Designing a Web-Based Tourism Package Application as a Promotional Tool for Tourism in Nusa Village - Ichsan; Ramadhani; Shabryana (LPPM Politeknik Aceh Selatan, 2023)
The tourism industry which is experiencing significant growth offers great potential to stimulate the economy of a region. This research aims to design and develop a web-based tour package application as a tourism promotion tool. This application uses the PHP programming language, uses the Laravel framework, and is integrated with the MySQL database. This application is designed to make it easier for users to find tour packages that suit their needs. Tourists can use this system to find out more detailed information regarding the list of available tour packages and make tour package orders. The stages in developing this application include stages such as needs analysis, interface design, system development using the PHP programming language with the Laravel framework, integration with the MySQL database, testing, and implementation.